A existência é corporal: o encontro da poética pessoal com as peles de Hundertwasser - Coser, Joao Victor (2023)
This research presents an excerpt of my poetic production, selected from the portfolio examination, presenting artistic works made between 2016 and 2020 [Casa Fragmentada (2016), Este Produto Contém (2016), Editorial de Autodestruição (2016), Processos Investigativos - Parte 1 (2018) e Desalinhamento Estrutural (2020)]. The analysis of the process uses the presentation of concepts and symbologies built by Hundertwasser on the skin, deriving in five skins concepts: the epidermis, clothing, home, social and global environment, as well as studying the support initial research, the body and the skin, understanding them as phenomenological factors. Connections of the chosen clipping are made with works by other artists, which deal with corporeality and the senses; as well as analyzing the languages present in each work, understanding the enlargement of performance and immersive spaces that solicit the body of the spectator, suggesting a performativity of 'oneself'. The analysis sought in the phenomenology of the body, assimilated by Merleau-Ponty and David Le Breton’s sociological direction as the construction of the Being and its surroundings. Tactile movement is the manipulation of the object or its materiality, visible or invisible, is also present as prerogatives of the body.